PENINGKATAN HASIL BELAJAR MELALUI MEDIA PERMAINAN GO GO EGG DI SEKOLAH DASAR - Arum Aprilia Sari; Muhammad Nur Wangid (Universitas Muria Kudus, 2021)
The purpose of this study is to improve student learning outcomes by using a game media called Go Go Egg. The game is adapted from a board game called Jumanji. The theme of this game is about introducing the diversity of Indonesian culture.The research method used is quasi-experimental with a one-group pretest-posttest research design. The subjects in this study were 19 fourth grade elementary school students. This research was conducted to see whether or not there was an increase in student learning outcomes before using the Go Go Egg game media and after using the Go Go Egg game media based on Indonesian cultural diversity. The data collection technique used was a written test in the form of multiple choice questions on the pretest and posttest with equivalent questions. The data analysis technique used in this research is the paired t-test.The results of the study of learning outcomes using the Go Go Egg game media an increase in the average value. The results at the pretest were 13.58 and increased at the posttest to 18.84. The conclusion from this study is that the Go Go Egg game can improve the learning outcomes of fourth grade elementary school students.